Physiologically based pharmacokinetic modeling in drug discovery and development: A pharmaceutical industry perspective. Issue 3 (9th January 2015) - Jones, HM; Chen, Y; Gibson, C; Heimbach, T; Parrott, N; Peters, SA; Snoeys, J; Upreti, VV; Zheng, M; Hall, SD
Abstract : The application of physiologically based pharmacokinetic (PBPK) modeling has developed rapidly within the pharmaceutical industry and is becoming an integral part of drug discovery and development. In this study, we provide a cross pharmaceutical industry position on "how PBPK modeling can be applied in industry" focusing on the strategies for application of PBPK at different stages, an associated perspective on the confidence and challenges, as well as guidance on interacting with regulatory agencies and internal best practices.